Feminism and Women with Disabilities - Serra, María Laura (The Age of Human Rights Journal, 2015)
Women with disabilities are doubly discriminated against and socially excluded: through gender and disability. In order to perform an in-depth analysis of their actual situation, it is necessary to understand which models have been able to provide legal and political answers to this issue. Hence, the feminist model can be identified, on the basis of which we might elaborate upon its possible ties with the social model of disability. This study shows the correctness of feminist conclusions when dealing with inequality between men and women, but it also proves the inaccurateness of feminism in its approach on women with disabilities.